Effect infection of cestode in some hematological standards in domestic chickens - aziz anah, Sadiya; sami alwan, Marwa; Abdul-Kader Al-Ibrahimi, Lubna (Al-Qadisiyah Journal of Pure Science, 2018)
This study was conducted to determine of haematological changes in local chicken infected with cestoda worms and compared with control group,50 samples of local chicken were collected at markt subsequent of AL-Diwaniyah city . Birds divided in to four groups ,G represent control group, G1 birds with light infection ,G2 birds with mediate infection ,G3 birds with severe infection. Haematology parametery include count total red blood corpuscles (Erythrocytic) and white blood cells (Leucocytic) ,Packed cell volume (P.C.V)% and Haemoglobin concentration (HB). The results showed that local chicken infected with two types of cestoda worm , Raillietina sp and Choanotonina infundibulum .and the percentage infection 78% . The result of blood examination showed that total erythrocytic count, packed cell volume , Hemoglobin percentage decreased significant in infected groups , while the total leucocytic count showed significant increased in all infected groups as compared with control groups.